Використання комунікацій та data-майнингу як ключових стратегічних ресурсів у публічному управлінні та адмініструванні - Ажажа, М. А.; Муц, Луай Файсал; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Oleksenko, Roman; Фурсін, О. О. (My University, 2020)
UK : Актуальність дослідження у тому, що використання комунікацій та data-майнингу як ключових стратегічних ресурсів у публічному управлінні та адмініструванні набуває великої практичної ваги, тому що інформаційні зміни трансформують культуру організації та сприяють її змінам. Мета статті – розвиток теоретичних та практичних засад комунікацій у публічному управлінні та адмініструванні, концептуалізація нових знань як чинників підвищення ефективності публічного управління та адміністрування. RU : Актуальность исследования в том, что использование коммуникаций и data-майнинга как ключевых стратегических ресурсов в публичном управлении и адмнистрировании приобретает большое практическое значение, потому что информцаионные изменения трансформируют культуру орагнизаций и содействуют ее изменениям. Цель статьи - развитие теоретических и практических оснований коммуникаций в публичном упрвлении и адмнистрировании, концептуализация новых знаний как факторов повышения эффективности публичного управления и адмнистрирования. Задачи исследования: 1) раскрыть, как коммуникационная функция руководителей предусматривает поддержание развития организации; 2) выяснить влияние коммуникационной функции на развитие публичного управления и администрирования; 3) раскрыть сущность использования принципов и методов data-майнинга как ключевого стратегического ресурса публичного управления и администрирования; 4) сформировать концепцию data-майнинга в публичном управлении и администрировании как фактора повышения эффективности публичного управления и администрирования; 5) обосновать направления оптимизации использования коммуникаций и data-майнинга как факторов повышения эффективности публичного управления и администрирования. EN : The relevance of the study is that the use of communications and data mining as key strategic resources in public administration is of great practical importance, because information change transforms the culture of the organization and contributes to its change. The purpose of the article is the development of theoretical and practical principles of communication in public administration and administration, conceptualization of new knowledge as factors to increase the efficiency of public administration. Objectives of the study: 1) to reveal how the communication function of managers involves maintaining the development of the organization; 2) to find out the influence of the communication function on the development of public administration; 3) identify the essence of the use of principles and methods of data mining as a key strategic resource of public administration and administration; 4) to form the concept of data-mining in public administration and administration as a factor in improving the efficiency of public administration; 5) to substantiate the directions of optimization of the use of communications and data-mining as factors to increase the efficiency of public administration and administration.
Использование коммуникаций и data-майнинга как ключевіх стратегических ресурсов в публичном управлении и администрировании
Use of communications and data mining as key strategic resources in public governance and administration
Keywords: публічне управління та адміністрування; майнинг даних; «data science»; комунікація; інформація; комунікативна компетентність; публичное управление и администрирование; майнинг данных; коммуникация; информация; коммуникативная компетентность; public administration and administration; data mining; data science; communication; information